College teaching in initial teacher training. the case of the school teacher of Segovia - José María Arribas Estebaranz; David Carabias Galindo; Inés Monreal Guerrero (Revista Electrónica Interuniversitaria de Formación del Profesorado)
This article shows the results of research conducted in the School of Education of Segovia, during the 2008-2009 school years about three fundamental aspects in the teaching-learning process: the methodology, the evaluation system and skills and competency development and professional teachers.This investigation is based primarily on analysis of the answers given by three groups of informants: teachers, students, seniors and graduate career. The instrument used is a validated questionnaire for each of these three aspects to our study.